The Relationship Between Psychological Capital and Organizational Culture with Organizational Citizenship Behavior among Outsourced Employees at PT. Pura Barutama - Ervana Damayanti; Nugraini Aprilia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to examine the relationship between psychological capital and organizational culture with Organizational Citizenship Behavior among outsourcing employees at PT Pura Barutama. Methodology: This study employed a quantitative correlational design to examine the relationships between psychological capital, organizational culture, and organizational citizenship behavior among 98 outsourced employees in Central Java, Indonesia. Participants were selected through purposive sampling based on specific inclusion criteria, and data were collected using validated questionnaires adapted to the Indonesian context. Statistical analyses included descriptive statistics, Pearson correlation, and hierarchical regression to assess relationships and predictive power between variables. Ethical guidelines were rigorously followed, ensuring informed consent, confidentiality, and data integrity throughout the research process. Main Findings: These findings indicate that the higher the psychological capital and the stronger the organizational culture, the greater the tendency for outsourcing employees to exhibit positive Organizational Citizenship Behavior in the workplace. Novelty/Originality of this study: This study takes a different subject than usual, namely outsourcing employees from PT Pura. It provides a little more understanding of how organizational culture and psychological capital can influence Organizational Citizenship Behavior among the outsourcing employees of PT Pura Barutama.